Beneficial effects of colchicine for moderate to severe COVID-19: a randomised, double-blinded, placebo-controlled clinical trial - Lopes, Maria Isabel; Bonjorno, Leticia P; Giannini, Marcela C; Amaral, Natalia B; Menezes, Pamella Indira; Dib, Saulo Musse; Gigante, Samara Libich; Benatti, Maira N; Rezek, Uebe C; Emrich-Filho, Laerte L; Sousa, Betania A A; Almeida, Sergio C L; et al. (Rheumatic & musculoskeletal diseases open, 2021)
ObjectiveTo evaluate whether the addition of colchicine to standard treatment for COVID-19 results in better outcomes.DesignWe present the results of a randomised, double-blinded, placebo-controlled clinical trial of colchicine for the treatment of moderate to severe COVID-19, with 75 patients allocated 1:1 from 11 April to 30 August 2020. Colchicine regimen was 0.5 mg thrice daily for 5 days, then 0.5 mg twice daily for 5 days. The primary endpoints were the need for supplemental oxygen, time of hospitalisation, need for admission and length of stay in intensive care unit and death rate.ResultsSeventy-two patients (36 for placebo and 36 for colchicine) completed the study. Median (and IQR) time of need for supplemental oxygen was 4.0 (2.0–6.0) days for the colchicine group and 6.5 (4.0–9.0) days for the placebo group (p<0.001). Median (IQR) time of hospitalisation was 7.0 (5.0–9.0) days for the colchicine group and 9.0 (7.0–12.0) days for the placebo group (p=0.003). At day 2, 67% versus 86% of patients maintained the need for supplemental oxygen, while at day 7, the values were 9% versus 42%, in the colchicine and the placebo groups, respectively (log rank; p=0.001). Two patients died, both in placebo group. Diarrhoea was more frequent in the colchicine group (p=0.26).ConclusionColchicine reduced the length of both, supplemental oxygen therapy and hospitalisation. The drug was safe and well tolerated. Once death was an uncommon event, it is not possible to ensure that colchicine reduced mortality of COVID-19.Trial registration numberRBR-8jyhxh.